Openness to mystical experience and psychological type: a study among Italians - Francis, Leslie J. (Mental health, religion & culture, 2017)
This study examines Ross’ thesis that intuitive types are more open than sensing types to mystical experience among a sample of 1155 Italians who completed the Francis Psychological Type Scales alongside the Mystical Orientation Scale. The data supported Ross’ thesis. Intuitive types recorded a significantly higher mean score than sensing types on the index of mystical orientation. Ranking the 16 complete types according to their mean mystical orientation scores located INFPs with the highest scores and ISTJs with the lowest scores.